2022
DOI: 10.1186/s13071-021-05124-3
|View full text |Cite
|
Sign up to set email alerts
|

Ivermectin as an endectocide may boost control of malaria vectors in India and contribute to elimination

Abstract: Malaria constitutes one of the largest public health burdens faced by humanity. Malaria control has to be an efficient balance between diagnosis, treatment and vector control strategies. The World Health Organization currently recommends indoor residual spraying and impregnated bed nets as two malaria vector control methods that have shown robust and persistent results against endophilic and anthropophilic mosquito species. The Indian government launched the National Framework for Malaria Elimination in 2016 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…New methods for malaria vector control should be considered for implementation in Hainan, as some studies in other countries have indicated there are methods that can significantly reduce mosquito populations. These were included: (1) attractive toxic sugar baits, which exploit the need for both male and female mosquitoes to take sugar meals [ 91 , 92 ]; (2) new insecticides such as broflanilide applied for IRS [ 93 , 94 , 95 ]; and (3) treating cattle with ivermectin to reduce the mosquito population in certain areas [ 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…New methods for malaria vector control should be considered for implementation in Hainan, as some studies in other countries have indicated there are methods that can significantly reduce mosquito populations. These were included: (1) attractive toxic sugar baits, which exploit the need for both male and female mosquitoes to take sugar meals [ 91 , 92 ]; (2) new insecticides such as broflanilide applied for IRS [ 93 , 94 , 95 ]; and (3) treating cattle with ivermectin to reduce the mosquito population in certain areas [ 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Africa's endemic regions, ivermectin trials have been carried out and have been reported with encouraging outcomes. 68 According to Mekuriaw et al's study, mosquitoes that fed on blood treated with ivermectin displayed a higher mortality rate compared with the control group. 69 Further research has shown that administering standard veterinary doses of ivermectin to cattle results in a significant decrease in the survival rates of An.…”
Section: Ivermectin-like Endectocidesmentioning
confidence: 99%
“…Therefore, expansion of indications for use of ivermectin should be feasible. 50 Toxic Sugar Baits: Traps with and without attractant (Toxic Sugar Bait/Attractive Toxic Sugar Bait) are being tested in Africa, Israel and USA. These can be useful as an outdoor vector control tool against malaria and dengue vectors.…”
Section: Introductionmentioning
confidence: 99%